Na rozdrożu. Posoborowe poszukiwania modeludla teologii - Paluch, Michał (Warszawskie Studia Teologiczne, 2019)
The paper presents two different post-conciliar projects of theology presented by Hans Küng (Menschwerdung Gottes) and by Marie-Joseph Le Guillou (Le mystère du Père). According to the first one, we need to develop theology on the basis of the Hegelian synthesis that presents an opportunity to reconcile Christianity with modernity. Such a development leads to a transgression of the teaching of the Ecumenical Councils of the first millennium with the hope of putting into practice their deep intentions. According to the second one, we should find the courage to judge contemporary philosophy in the light of theological principles established during the first millennium (regula fidei). The divine eternal plan of salvation should become the decisive perspective to develop sound theology and to correct its various errors. Although both proposals have been presented ca. 50 years ago, the choice between them seems still of crucial importance.